Near-infrared light driven degradable surgical suture capable of self-constricting and accelerating wound healing as well as preparation method and application of near-infrared light driven degradable surgical suture

Degradable surgical sutures driven by near-infrared light-driven self-contraction and thermally controlled drug release solve the problem that traditional sutures are difficult to suture deep inside the body or in swollen tissue, and achieve efficient healing of wounds in patients with chronic wounds.

CN119455055AActive Publication Date: 2025-02-18UNIVERSITY OF HEALTH & REHABILITATION SCIENCES

Patent Information

Application Number
CN202411651871.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Traditional shape memory sutures are difficult to achieve effective sutures in deeper or swollen tissues inside the body, and wound healing in chronic wound patients is slow, and the prior art is difficult to solve these problems.

Method used

A near-infrared light-driven self-contraction degradable surgical suture was developed to modify the nanofiber sutures through copper ion-mediated structural functions of polydopamine networks and coat gelatin on its surface to achieve drug release, synergistically accelerate wound healing.

Benefits of technology

The suture can self-contract under near-infrared light drive, remotely regulate wound density, solve internal wound suture problems, and accelerate wound healing through thermal control drug release, and is suitable for chronic wound patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455055A_ABST
    Figure CN119455055A_ABST
Patent Text Reader

Abstract

The invention relates to a degradable surgical suture capable of self-constricting under the driving of near-infrared light and accelerating wound healing as well as a preparation method and application of the degradable surgical suture, and the degradable surgical suture capable of self-constricting under the driving of the near-infrared light is developed by virtue of a photo-thermal conversion effect of polydopamine on the basis of a thermal response characteristic of a shape memory material. And on the basis, a thermal control drug release system is endowed to the suture line to synergistically accelerate the wound healing process, and various suture problems confronted by the internal wound of the body are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a degradable surgical suture thread which can self-shrink and accelerate wound healing driven by near-infrared light, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to increase some understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to ordinary technicians in this field.

[0003] Suturing incisions after surgical operations can accelerate wound healing, reduce infection and scar formation. When suturing wounds, attention should be paid to suture tension. On the one hand, it is necessary to ensure tight closure to prevent scar formation; on the other hand, the suture should not be too tight to cause necrosis of tissue around the wound. However, it is very difficult to accurately control the suture force in a limited space during suture surgery. To this end, a variety of shape memory sutures have been developed by researchers (CN200710072406.0; CN117338360A), and on this basis, active molecules are further modified to give sutures additional functions, such as antibacterial (DOI: 10.1016 / j.cclet.2019.11.006). However, traditional shape memory sutures generally use thermal actuation to achieve self-contraction. Although it has certain efficacy, it is limited by spatiotemporal response. For example, thermal actuation is not suitable for deeper wounds or swollen tissues inside the body, and sutures in these specific scenarios have not yet received attention from researchers. For patients with chronic wounds, slow wound healing is also a clinical problem that patients urgently need to solve. Summary of the invention

[0004] In view of the shortcomings of the prior art and in view of the tissue penetrability of near-infrared light, the present invention has developed a near-infrared light-driven self-contracting biodegradable surgical suture based on the thermal response characteristics of shape memory materials and the photothermal conversion effect of polydopamine. On this basis, the suture is endowed with a thermally controlled drug release system to synergistically accelerate the wound healing process and solve the various suturing problems faced by internal wounds of the body.

[0005] The technical solution adopted by the present invention is as follows:

[0006] In a first aspect of the present invention, a method for preparing a degradable surgical suture that is self-shrinking and accelerates wound healing driven by near-infrared light is provided, the method comprising the following steps:

[0007] Copper ion-mediated polydopamine network structure (PDA-Cu) functional modified nanofiber suture: dopamine (DA) and copper salt were dissolved in buffer to prepare DA / Cu 2+A mixed solution is prepared; a fiber membrane of polylactic acid / polyhydroxybutyric acid valeric acid copolyester (PLLA / PHBV) is immersed in the solution and shaken; the fiber membrane is taken out and washed to obtain a nanofiber membrane modified with PDA-Cu function; the nanofiber membrane is twisted into a thread to obtain a fiber suture thread modified with PDA-Cu function;

[0008] Gelatin (Gel) surface coated nanofiber suture: gelatin was dissolved in PBS solution; then EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide) and NHS (N-hydroxysuccinimide) in a set ratio were added to the gelatin solution and stirred;

[0009] Then, the nanofiber suture thread modified with PDA-Cu function is added for immersion, taken out and cooled, and after gelatin cross-linking, the degradable surgical suture thread that can self-shrink and accelerate wound healing driven by near-infrared light is obtained.

[0010] In one or some embodiments of the present invention, in the step of PDA-Cu functional modification of nanofiber sutures, the copper salt includes but is not limited to copper chloride; the mass ratio of dopamine and copper salt is (1-100): 1, DA / Cu 2+ The concentration of dopamine in the mixed solution is 0.1-10 mg / mL; preferably, the mass ratio of dopamine to copper salt is (1-50):1; more preferably, the mass ratio of dopamine to copper salt is 4:1, DA / Cu 2+ The concentration of dopamine in the mixed solution was 2 mg / mL.

[0011] In one or some embodiments of the present invention, in the step of PDA-Cu functional modification of nanofiber sutures, the oscillation is a slight oscillation, and the oscillation frequency is 0 to 500 rpm, excluding 0.

[0012] In one or some embodiments of the present invention, in the step of PDA-Cu functional modification of nanofiber sutures, the buffer is Tris-HCl buffer; the concentration is 5-20 mM, pH 5-10.

[0013] In one or some embodiments of the present invention, in the step of PDA-Cu functional modified nanofiber suture, the fiber membrane with directional arrangement of PLLA / PHBV can be prepared by the method in the prior art. The present invention provides a preferred method for preparing a fiber membrane with directional arrangement of PLLA / PHBV by stable jet electrospinning technology. Specifically comprising the following steps: dissolving PLLA and PHBV in a hexafluoroisopropanol (HFIP) solution to prepare a spinning solution, stirring until a transparent and uniform solution is formed, and preparing directional arrangement of PLLA / PHBV ultrafine fibers based on a stable jet electrospinning method. The present invention selects PLLA / PHBV fibers as the basic fiber structure of degradable surgical sutures based on excellent mechanical properties and shape recovery properties. After experimental verification, the stable jet electrospinning technology of the present invention can prepare a PLLA / PHBV fiber membrane with a smooth surface, and each fiber presents a certain longitudinal arrangement. The prepared PLLA / PHBV fiber membrane has significant shape recovery performance, and the shape recovery ability is as high as 95% under heating conditions.

[0014] Preferably, the mass ratio of PLLA to PHBV is 5-8:3-6; more preferably, the mass ratio of PLLA to PHBV is 6:4.

[0015] Preferably, the molecular weight of PLLA is 100,000 Daltons or less; more preferably, the molecular weight of PLLA is 100,000 Daltons.

[0016] Preferably, the content of hydroxyvaleric acid in PHBV is 1-10 mol%, and the molecular weight is 520,000 Daltons or less; more preferably, the content of hydroxyvaleric acid in PHBV is 2.9 mol%, and the molecular weight is 520,000 Daltons.

[0017] Preferably, the concentration of the spinning solution is 10-14% (w / v), which means that 100 mL of the solution contains (10-14) g PLLA and PHBV; more preferably, the concentration of the spinning solution is 12% (w / v).

[0018] Preferably, the spinning parameters are: voltage 6 kV, injection rate 0.5 mL / h, receiving distance 10 cm, drum speed 1000 rpm, room temperature, and ambient humidity 70-90%.

[0019] In one or some embodiments of the present invention, in the step of Gel surface coating nanofiber suture, the mass volume ratio of the gelatin and PBS solution is (1-20) g:100 mL; preferably, the mass volume ratio of the gelatin and PBS solution is 7.5 g:100 mL.

[0020] In one or some embodiments of the present invention, in the step of coating the surface of the Gel nanofiber suture, the mass ratio of EDC to NHS is (2-8):3; preferably, the mass ratio of EDC to NHS is 5:3.

[0021] In one or some embodiments of the present invention, in the step of coating the surface of the Gel nanofiber suture, the immersion time is 5 to 300 s; preferably, the immersion time is 10 to 200 s; more preferably, the immersion time is 30 s.

[0022] In a second aspect of the present invention, a degradable surgical suture which is prepared by the above method and driven by near-infrared light and which self-shrinks and accelerates wound healing is provided.

[0023] In a third aspect of the present invention, there is provided use of the degradable surgical suture in the preparation of medical supplies.

[0024] Compared with the related art known to the inventor, one of the technical solutions of the present invention has the following beneficial effects:

[0025] The present invention comprehensively utilizes shape memory materials and the photothermal effect of PDA to develop a near-infrared light-driven self-contracting degradable surgical suture.

[0026] The present invention comprehensively utilizes shape memory materials, the photothermal effect of PDA and the gel-sol transformation performance of Gel to develop a degradable surgical suture with controllable drug release driven by near-infrared light, which can accelerate wound healing in the sutured area.

[0027] The present invention can not only remotely control the tightness of wound closure as needed under the drive of near-infrared light, but also release active ingredients to accelerate wound healing, and no stitches need to be removed after surgery. In addition to basic suturing of damaged tissues or organs after surgery, it has more application advantages in scenarios where the operating space of wounds inside the body is limited (such as minimally invasive surgery) and the shape of sutured tissues or organs changes after surgery (such as swelling of swollen tissues).

[0028] The near-infrared light-driven self-shrinking and wound-healing-accelerating degradable surgical sutures of the present invention have the following functions: 1) The near-infrared light-driven sutures heat up to self-shrink, thereby accelerating wound closure. The tightness of the wound can be remotely controlled to solve the problem of difficult precision suturing of wounds inside the body, or the problem of loose wounds after swelling of swollen tissues after suturing, or the problem of easy shape changes of other tissues in the body after suturing; 2) The near-infrared light-driven sutures heat up to accelerate drug release and promote wound repair. This is extremely important for patients with chronic diseases, as it can prevent infection and scar formation caused by persistent non-closure of wounds. Figure 1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1 Schematic diagram of wound tissue changes caused by near-infrared light-driven sutures.

[0031] Figure 2 Schematic diagram of the preparation principle of nanofiber sutures with gelatin surface coating.

[0032] Figure 3 Morphological observation (fiber film and processed fiber bundle). PP: PLLA / PHBV fiber;

[0033] PDA-Cu@PP: fibers functionally modified with PDA-Cu; Gel@PDA-Cu@PP: nanofibers further surface-coated with gelatin.

[0034] Figure 4 Analysis of shape memory and photothermal effects: (A) Mechanical properties of PP at different temperatures; (B) Shape memory effect of PP; (C) Changes in shape recovery force with increasing temperature; (DE) Temperature changes of materials under 0.5W near-infrared light; (FG) Temperature changes of materials under near-infrared light of different powers; (H) Shape recovery performance; (I) Drug release stimulated by near-infrared light.

[0035] Figure 5 Material biocompatibility assessment: (A) cell adhesion and cell morphology; (B) Collagen I expression.

[0036] Figure 6 NIR stimulates suture contraction to promote skin healing: (A) Wound closure under NIR stimulation; (B) Wound healing under NIR stimulation.

[0037] Figure 7 NIR stimulates suture contraction to promote wound repair: (A) histological staining; (BF) quantitative analysis. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0039] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0041] Example 1

[0042] The schematic diagram of the preparation principle is as follows Figure 2 .

[0043] ① PLLA / PHBV fiber membrane was prepared by stable jet electrospinning technology: PLLA (Mv = 100,000Da) and PHBV (520,000Da) were weighed and dissolved in HFIP solution at a mass ratio of 6:4 to prepare a spinning solution with a total concentration of 12% (w / v), and stirred on a magnetic stirrer for more than 14 hours until a transparent and uniform solution was formed. Then, PLLA / PHBV directional ultrafine fibers were prepared based on the stable jet electrospinning method, and the spinning parameters were: voltage 6kV, injection rate 0.5mL / h, receiving distance 10cm, drum speed 1000rpm, room temperature, and ambient humidity 70-90%.

[0044] ②PDA-Cu functional modified nanofiber suture: Dopamine (DA, 2 mg / mL) and copper chloride (0.5 mg / mL) were dissolved in Tris-HCl (10 mM, pH 8.5) buffer to prepare DA / Cu 2+ Mix the solution; then immerse the fiber membrane in the solution and gently oscillate at room temperature for 12 hours at a frequency of 100 rpm; take out the fiber membrane, wash it with ultrapure water for multiple times to obtain a nanofiber membrane modified with PDA-Cu functionality; then twist it into a thread to obtain a nanofiber suture thread modified with PDA-Cu functionality.

[0045] ③ Gel surface coated nanofiber suture: Dissolve gelatin in PBS solution at a mass volume ratio of 7.5%, and stir at 50°C for 6 hours to fully dissolve; then add EDC and NHS to the gelatin solution at a mass ratio of 5:3 and stir for 5 minutes; then add PDA-Cu functionally modified nanofiber suture and soak for 30 seconds, and cool naturally until the gelatin is fully cross-linked.

[0046] like Figure 3As shown in the figure, the stable jet electrospinning technology can prepare a smooth surface of PLLA / PHBV oriented fiber membrane (named PP), and each fiber shows a certain longitudinal arrangement; after PDA-Cu functional modification (named PDA-Cu@PP), obvious particle deposition can be seen on the fiber surface; after further coating with gelatin (named Gel@PDA-Cu@PP), the fiber diameter becomes thicker and adhesion is formed between the fibers. These results show that we have successfully prepared PP fiber bundles modified with Gel and PDA-Cu functions.

[0047] like Figure 4 As shown in (A), when the temperature rises to 55°C, the mechanical properties of the PP fiber membrane decrease significantly, indicating that temperature can change the mechanical properties of the PP fiber membrane. On this basis, we observed that the PP fiber has significant shape recovery performance, and the shape recovery ability under heating conditions is as high as 95% ( Figure 4 (B)); Next, we analyzed the shape recovery of the material and found that PDA-Cu was beneficial to improving the shape recovery of the material. Although the shape recovery decreased after Gel modification, it was still higher than PP ( Figure 4 (C)); When the material was exposed to near-infrared light, it was found that the PP fiber membrane had no photothermal effect, but the photothermal effect was obvious after PDA-Cu modification ( Figure 4 (D)), and the heating rate was increased after Gel modification ( Figure 4 (E)). This may be attributed to the heat preservation effect of Gel. Similarly, under the irradiation of near-infrared light of different powers, the photothermal effect of Gel@PDA-Cu@PP fiber bundles also varies ( Figure 4 (F)). For example, as the near-infrared light power increases, the heating rate of the fiber bundle increases significantly ( Figure 4 (G)). These results indicate that it is possible to achieve shape memory recovery of the material by stimulating the temperature rise of the material under near-infrared light irradiation. Based on this, we further used near-infrared light to observe the shape recovery performance of the Gel@PDA-Cu@PP material and found that the stretched plastic fiber bundles can be well restored to their initial shape under NIR stimulation ( Figure 4 (H)). More interestingly, NIR stimulation can significantly enhance the gel-sol transition of Gel, achieving NIR-controlled drug release ( Figure 4 (I)).

[0048] like Figure 5As shown in (A), PDA-Cu modification can significantly promote fibroblast adhesion, and the promotion effect is further enhanced after Gel modification; similarly, when the cells are cultured for 24 hours, it can be observed that PDA-Cu modification significantly enhances the stress fiber remodeling of the cells, and Gel modification is also conducive to the formation of the cytoskeleton. From a functional point of view, PDA-Cu modification is conducive to promoting collagen expression, but gelatin expression is significantly reduced after Gel modification ( Figure 5 (B)). This can be attributed to the presence of Gel compensating for the content of microenvironmental collagen, thereby reducing cellular collagen secretion. Therefore, the release of Gel under NIR irradiation further reduced the secretion of Collagen I.

[0049] like Figure 6 As shown in (A), after the wound was sutured with Gel@PDA-Cu@PP suture, the contraction of the suture was significantly promoted under NIR irradiation, thereby promoting wound closure. The wound was observed until 14 days, and it was observed that in the blank group without wound suture, obvious unclosed areas were still visible at the wound ( Figure 6 (B)); The wound healing rate of PP sutures was significantly improved after suturing, and the healing rate of sutures coated with Gel was even higher. Interestingly, after NIR light irradiation, obvious hair regeneration was observed. This indicates that suture contraction and Gel release caused by NIR stimulation can significantly improve wound healing.

[0050] like Figure 7 As shown in (A), compared with the Blank group, PP sutures can significantly promote tissue remodeling in the wound area; Gel modification can significantly promote skin regeneration ( Figure 7 (B)), and wound healing was basically achieved under NIR stimulation, and obvious hair follicle regeneration and epithelialization were observed ( Figure 7 (C)). Masson staining results also confirmed that PP sutures can promote collagen formation, and Gel modification can also promote collagen remodeling and maturation. This phenomenon is further enhanced under NIR light. CD31, CD206 and TNF-α immunofluorescence staining results also further confirmed that Gel@PDA-Cu@PP sutures can significantly promote wound vascularization under NIR stimulation ( Figure 7 (D)), while reducing excessive inflammatory responses ( Figure 7 (E)-(F)), thereby promoting skin healing.

[0051] In summary, the present invention successfully prepared a NIR-driven self-contracting degradable surgical suture, and proved that it can not only accelerate wound closure by utilizing its own shape recovery property, but also realize controlled drug release under NIR stimulation, further accelerating wound repair.

[0052] Example 2

[0053] ① The PLLA / PHBV oriented fiber membrane was prepared by stable jet electrospinning technology: PLLA (Mv = 100,000Da) and PHBV (520,000Da) were weighed and dissolved in HIFP solution at a mass ratio of 7:3 to prepare a spinning solution with a total concentration of 10% (w / v), and stirred on a magnetic stirrer for more than 14 hours until a transparent and uniform solution was formed. Then, PLLA / PHBV oriented ultrafine fibers were prepared based on the stable jet electrospinning method, with spinning parameters: voltage 6kV, injection rate 0.5mL / h, receiving distance 10cm, drum speed 1000rpm, room temperature, and ambient humidity 70-90%.

[0054] ②PDA-Cu functional modified nanofiber suture: DA (5 mg / mL) and copper chloride (1 mg / mL) were dissolved in Tris-HCl (10 mM, pH 8.5) buffer to prepare DA / Cu 2+ Mix the solution; then immerse the PLLA / PHBV directional fiber membrane in the solution and gently oscillate at room temperature for 6 hours at a frequency of 200 rpm; take out the fiber membrane, wash it with ultrapure water for multiple times to obtain a PDA-Cu functionally modified nanofiber membrane; then twist it into a thread to obtain a PDA-Cu functionally modified nanofiber suture thread.

[0055] ③Gel surface coated nanofiber suture: Dissolve gelatin in PBS solution at a mass volume ratio of 5%, and stir at 50°C for 6 hours to fully dissolve; then add EDC and NHS to the gelatin solution at a mass ratio of 5:3 and stir for 5 minutes; then immediately add PDA-Cu functionally modified nanofiber suture and soak for 60 seconds, cool naturally until the gelatin is fully cross-linked to obtain a degradable surgical suture that can be driven by near-infrared light to self-shrink and accelerate wound healing.

[0056] Example 3

[0057] ① The PLLA / PHBV oriented fiber membrane was prepared by stable jet electrospinning technology: PLLA (Mv = 100,000Da) and PHBV (520,000Da) were weighed and dissolved in HFIP solution at a mass ratio of 8:2 to prepare a spinning solution with a total concentration of 8% (w / v), and stirred on a magnetic stirrer for more than 14 hours until a transparent and uniform solution was formed. Then, PLLA / PHBV oriented ultrafine fibers were prepared based on the stable jet electrospinning method, with spinning parameters: voltage 6kV, injection rate 0.5mL / h, receiving distance 10cm, drum speed 1000rpm, room temperature, and ambient humidity 70-90%.

[0058] ②PDA-Cu functional modified nanofiber membrane: DA (8 mg / mL) and copper chloride (1 mg / mL) were dissolved in Tris-HCl (10 mM, pH 8.5) buffer to prepare DA / Cu 2+ A mixed solution was prepared; the PLLA / PHBV directional fiber membrane was immersed in the solution and gently oscillated at room temperature for 6 hours at a frequency of 100 rpm; the fiber membrane was taken out and washed with ultrapure water for multiple times to obtain a PDA-Cu functionally modified nanofiber membrane; the nanofiber suture thread was twisted into a thread to obtain a PDA-Cu functionally modified nanofiber membrane.

[0059] ③Gel surface coated nanofiber suture: Dissolve gelatin in PBS solution at a mass volume ratio of 3%, and stir at 50°C for 6 hours to fully dissolve; then add EDC and NHS to the gelatin solution at a mass ratio of 5:3 and stir for 5 minutes; then immediately add PDA-Cu functionally modified nanofiber suture and soak for 100 seconds, cool naturally until the gelatin is fully cross-linked to obtain a degradable surgical suture that can be driven by near-infrared light to self-shrink and accelerate wound healing.

[0060] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a degradable surgical suture that is self-contracting and accelerates wound healing driven by near-infrared light, characterized in that: The method comprises the following steps: Copper ion-mediated polydopamine network structure (PDA-Cu) functional modified nanofiber suture: dopamine (DA) and copper salt were dissolved in buffer to prepare DA / Cu 2+ A mixed solution is prepared; a fiber membrane of polylactic acid / polyhydroxybutyric acid valeric acid copolyester (PLLA / PHBV) is immersed in the solution and shaken; the fiber membrane is taken out and washed to obtain a nanofiber membrane modified with PDA-Cu function; the nanofiber membrane is twisted into a thread to obtain a fiber suture thread modified with PDA-Cu function; Gelatin (Gel) surface coated nanofiber suture: gelatin was dissolved in PBS solution; then EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide) and NHS (N-hydroxysuccinimide) in a set ratio were added to the gelatin solution and stirred; Then, the nanofiber suture thread modified with PDA-Cu function is added for immersion, taken out and cooled, and after gelatin cross-linking, the degradable surgical suture thread that can self-shrink and accelerate wound healing driven by near-infrared light is obtained.

2. The method for preparing the degradable surgical suture thread that is driven by near-infrared light to self-shrink and accelerate wound healing as claimed in claim 1, characterized in that: In the step of PDA-Cu functional modification of nanofiber suture, the copper salt is copper chloride; the mass ratio of dopamine and copper salt is (1-100): 1, DA / Cu 2+ The concentration of dopamine in the mixed solution is 0.1-10 mg / mL.

3. The method for preparing the degradable surgical suture thread that is driven by near-infrared light to self-shrink and accelerate wound healing as claimed in claim 1, characterized in that: In the step of PDA-Cu functionally modified nanofiber suture, the oscillation is a slight oscillation, and the oscillation frequency is 0 to 500 rpm, excluding 0.

4. The method for preparing the degradable surgical suture thread that is driven by near-infrared light to self-shrink and accelerate wound healing as claimed in claim 1, characterized in that: In the step of functionally modifying the nanofiber suture with PDA-Cu, the buffer is Tris-HCl buffer with a concentration of 5 to 20 mM and a pH of 5 to 10.

5. The method for preparing the degradable surgical suture thread that is driven by near-infrared light to self-shrink and accelerate wound healing as claimed in claim 1, characterized in that: In the step of PDA-Cu functional modified nanofiber suture, a PLLA / PHBV oriented fiber membrane was prepared by stable jet electrospinning technology; Specifically include the following steps: PLLA and PHBV are dissolved in HIFP solution to prepare a spinning solution, which is stirred to prepare PLLA / PHBV oriented ultrafine fibers based on a stable jet electrospinning method; Preferably, the mass ratio of PLLA to PHBV is 5-8:3-6; Preferably, the molecular weight of PLLA is 100,000 or less Daltons; Preferably, the content of hydroxyvaleric acid in PHBV is 1-10 mol%, and the molecular weight is 520,000 Daltons or less; Preferably, the concentration of the spinning solution is 10 to 14% (w / v); Preferably, the spinning parameters are: voltage 6 kV, injection rate 0.5 mL / h, receiving distance 10 cm, drum speed 1000 rpm, room temperature, and ambient humidity 70-90%.

6. The method for preparing a degradable surgical suture that is self-contracting and accelerates wound healing driven by near-infrared light as claimed in claim 1, wherein Ge In the step of surface coating the nanofiber suture, the mass volume ratio of the gelatin and PBS solution is (1-20) g:100 mL.

7. The method for preparing a degradable surgical suture that is self-contracting and accelerates wound healing driven by near-infrared light as claimed in claim 1, wherein Ge In the step of surface coating the nanofiber suture, the mass ratio of EDC to NHS is (2-8):

3.

8. The method for preparing the degradable surgical suture thread that is self-shrinking and accelerates wound healing driven by near-infrared light as claimed in claim 1, characterized in that: In the step of coating the nanofiber suture on the surface of Gel, the immersion time is 5 to 300 seconds.

9. A degradable surgical suture thread that is self-shrinking and accelerates wound healing and is prepared by the method according to any one of claims 1 to 8.

10. Use of the degradable surgical suture according to claim 9 in the preparation of medical supplies.

Citation Information

Patent Citations

  • Biodegradable shape memory stitched wire

    CN101332310A

  • Self-expanding and tightening non-absorbent surgical suture

    CN117338360A

  • Preparation method of polydopamine / polylactic acid / nano-copper composite fiber membrane with photo-thermal / copper synergistic antibacterial function

    CN112575576A

  • Photo-thermal antibacterial silk fiber film as well as preparation method and application thereof

    CN117144673A

  • Woven polylactic acid antibacterial surgical suture and preparation method thereof

    CN118022036A

Cited By

  • Near-infrared two-region photosensitive molecule, preparation method and application of near-infrared two-region photosensitive molecule in preparation of suture line

    CN121045213A

  • An intelligent braided material with wet-pH dual response characteristics and a preparation method and application thereof

    CN122707315A